Research methods in human-computer interaction - Lazar, Jonathan; Feng, Jinjuan Heidi; Hochheiser, Harry (Chichester : Wiley, 2010)
'Continual technological evolution has led to an explosion of new techniques in Human-Computer Interaction (HCI) research. Research Methods in Human-Computer Interaction is a comprehensive guide to performing research and is essential reading for both quantitative and qualitative methods. Chapters cover a broad range of topics relevant to the collection and analysis of HCI data, going beyond experimental design and surveys, to cover ethnography, time diaries, physiological measurements, case studies, and other essential elements in the well-informed HCI researcher's toolkit.'--BOOK JACKET.
Experimental research -- Experimental design -- Statistical analysis -- Surveys -- Diaries -- Case studies -- Interviews and focus groups -- Ethnography -- Usability testing -- Analyzing qualitative data -- Automated data collection methods -- Measuring the human -- Working with human subjects -- Working with research participants with impairments.
Includes bibliographical references and index.
Keywords: Human-computer interaction -- Research